HIPOTESIS SAPIR-WHORF DAN TATA PERGAULAN GENERASI MUDA - Diana Hardiyanti (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2011)
This paper deals with language, culture and thought of the young generation in the society. How they interact among others. Is the eastern culture of Indonesian’s heritage still remaining in the youth?  Interrelationship between language, culture, and thought becomes the basic idea of the Sapir and Whorf hypothesis. The paper will analyze the song lyrics that famous among the youth. How this hypothesis works in the analysis of song lyrics. And can this hypothesis be used to determine the correlation between language, culture and thought of the youth that were written in the lyrics.